Power and loss in South African journalism : news in the age of social media - Daniels, Glenda (Wits University Press, 2020)
This timely collection analyses the crisis of journalism in contemporary South Africa. Writing with authority as a seasoned journalist, the author addresses the gains and losses from decolonial and feminist perspectives and sees opportunities to forge a model for non-profit, public-funded journalism that reflects a diversity of voices.